Polarisation of human macrophages towards an M1 subtype triggered by an atypical Brazilian strain of Toxoplasma gondii results in a reduction in parasite burden - Guimaraes Gois, Paula Suellen; Franco, Priscila Silva; Cota Teixeira, Samuel; Guirelli, Pamela Mendonca; de Araujo, Thadia Evelyn; da Fonseca Batistao, Deivid William; de Oliveira, Fernanda Chaves; Licia Santos Ferreira, Gabriela; de Oliveira Gomes, Angelica; Favoreto, Silvio; Mineo, Jose Roberto; de Freitas Barbosa, Bellisa; et al. (Folia parasitologica, 2022)
Toxoplasma gondii Nicolle et Manceaux, 1909, the etiologic agent of toxoplasmosis, was considered a clonal population with three distinct genetic lineages (I, II and III); however, sequence analysis of different strains has revealed distinct atypical genotypes. Macrophages are essential for immunity against toxoplasmosis and differential cell regulation may affect the course of the disease. In this context, our study aims to investigate the infection by TgChBrUD2, a highly virulent atypical Brazilian strain of T. gondii, on the activation and polarisation of human macrophages. Human macrophage-like cells obtained from THP-1 cells were infected with TgChBrUD2, RH or ME49 strains of T. gondii to evaluate the impact of parasite infection on macrophage polarisation. Our results indicate that the TgChBrUD2 and ME49 strains of T. gondii induced a classic activation of human macrophages, which was confirmed by the high rate of spindle-shaped macrophages, low amount of urea and increase in the levels of nitrite, as well as the down-regulation of M2-markers. In contrast, RH strain promoted an alternative activation of macrophages. The polarisation of human macrophages towards an M1 subtype mediated by TgChBrUD2 and ME49 strains resulted in a low parasite burden, with high levels of IL-6 and MIF. Finally, the M2 subtype triggered by the RH strain culminated in a lower intracellular proliferation index. We concluded that the atypical (TgChBrUD2) and clonal (ME49) strains are able to elicit an M1 subtype, which results in parasitism control, partially explained by the high levels of IL-6 and MIF produced during the infection by these genotypes. In contrast, the clonal (RH) strain promoted a macrophage polarisation towards an M2 subtype, marked by a high parasite burden, with a weak modulation of pro-inflammatory cytokines. Thus, atypical strains can present different mechanisms of pathogenicity and transmissibility compared to clonal strains, as well as they can use distinct strategies to evade the host's immune response and ensure their survival.
Keywords: macrophage polarisation; Animals; paraziti; Cytokines; močovina; Toxoplasmosis; makrofágy; Brazil; dusitany; cytokiny; lidé; Macrophages; Toxoplasma; Interleukin-6; TgChBrUD2 strain; Parasites; clonal strains; interleukin-6; Brazílie; toxoplazmóza; toxoplasmosis; zvířata; Urea; Nitrites; Humans